Targeting NMDA receptor in Alzheimer’s disease: identifying novel inhibitors using computational approaches - Siddiqui, Arif Jamal; Badraoui, Riadh; Jahan, Sadaf; Alshahrani, Mohammed Merae; Siddiqui, Maqsood Ahmed; Khan, Andleeb; Adnan, Mohd (Frontiers in Pharmacology, 2023)
The glutamate-gated ion channels known as N-methyl-d-aspartate receptors (NMDARs) are important for both normal and pathological brain function. Subunit-selective antagonists have high therapeutic promise since many pathological conditions involve NMDAR over activation, although few clinical successes have been reported. Allosteric inhibitors of GluN2B-containing receptors are among the most potential NMDAR targeting drugs. Since the discovery of ifenprodil, a variety of GluN2B-selective compounds have been discovered, each with remarkably unique structural motifs. These results expand the allosteric and pharmacolog-ical spectrum of NMDARs and provide a new structural basis for the development of next-generation GluN2B antagonists that have therapeutic potential in brain diseases. Small molecule therapeutic inhibitors targeting NMDA have recently been developed to target CNS disorders such as Alzheimer's disease. In the current study, a cheminformatics method was used to discover potential antagonists and to identify the structural requirements for Gly/NMDA antagonism. In this case we have created a useful pharmacophore model with solid statistical values. Through pharmacophore mapping, the verified model was used to filter out virtual matches from the ZINC database. Assessing receptor-ligand binding mechanisms and affinities used molecular docking. To find the best hits, the GlideScore and the interaction of molecules with important amino acids were considered essential features. We found some molecular inhibitors with high binding affinity using computational methods. These molecules showed high binding affinity; they are -13.1, -12.88, -12.67, -12.56, -12.55 and -12.52 Kcal/mol compared to the control ifenprodil group (-10.29). The stability of molecules has also been determined by MD experiments and binding energy calculation. Moreover, these five leads have been proposed as potential new perspectives for exploring potent Gly/NMDA receptor antagonists. In addition, it can be tested in the laboratory for potential therapeutic strategies for both in vitro and in vivo research.